2019
DOI: 10.1096/fj.201900893r
|View full text |Cite
|
Sign up to set email alerts
|

Klotho regulation by albuminuria is dependent on ATF3 and endoplasmic reticulum stress

Abstract: Proteinuria is associated with renal function decline and cardiovascular mortality. This association may be attributed in part to alterations of Klotho expression induced by albuminuria, yet the underlying mechanisms are unclear. The presence of albumin decreased Klotho expression in the POD‐ATTAC mouse model of proteinuric kidney disease as well as in kidney epithelial cell lines. This downregulation was related to both decreased Klotho transcription and diminished protein half‐life, whereas cleavage by ADAM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 72 publications
3
8
0
Order By: Relevance
“…A minority of renal tubular cells take this transition further and migrate to the interstitium where, along with existing interstitial fibroblasts, they contribute directly to the production of extracellular matrix and fibrosis. Albumin exposure also directly, via an epigenetic mechanism, reduces Klotho expression in proximal tubular cells, which is believed to contribute to hyperphosphataemia, higher levels of fibroblast growth factor-23, and lower levels of circulating Klotho [34, 35]. This may, in part, explain the importance of albuminuria as a cardiovascular risk factor; a link demonstrated by the finding that, independent of changes in other biomarkers, albuminuria lowering explained 36% of the beneficial effect of canagliflozin on cardiovascular events [36].…”
Section: Proteinuria and Progressive Kidney Diseasementioning
confidence: 99%
“…A minority of renal tubular cells take this transition further and migrate to the interstitium where, along with existing interstitial fibroblasts, they contribute directly to the production of extracellular matrix and fibrosis. Albumin exposure also directly, via an epigenetic mechanism, reduces Klotho expression in proximal tubular cells, which is believed to contribute to hyperphosphataemia, higher levels of fibroblast growth factor-23, and lower levels of circulating Klotho [34, 35]. This may, in part, explain the importance of albuminuria as a cardiovascular risk factor; a link demonstrated by the finding that, independent of changes in other biomarkers, albuminuria lowering explained 36% of the beneficial effect of canagliflozin on cardiovascular events [36].…”
Section: Proteinuria and Progressive Kidney Diseasementioning
confidence: 99%
“…Particularly, activating transcription factor 3 (ATF3), a potential neuronal marker under pathology, was activated on small nociceptors in concert with skin denervation [ 10 ], suggesting that ATF3 is a critical marker in addition to noxious transduction by IENF. ATF3 has also been suggested to be a marker of ER stress, and it negatively affects ER stress in obesity-related diabetes [ 11 , 12 ] and in renal tissue failure [ 13 ] due to obesity-lipotoxicity-induced ATF3 activation and ER stress. ATF3 has paradoxical regulatory roles; ATF3 deficiency suppresses transplant rejection by ameliorating the inflammatory response [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Delitsikou et al demonstrated an association between ER stress activation and reduced Klotho protein levels, and specific inhibition of ER stress restored Klotho protein expression without changing klotho mRNA levels in a proteinuria CKD model [21]. This study was the first to reveal that enhanced Klotho degradation was associated with a loss of Klotho expression, but the exact mechanism remained to be elucidated.…”
Section: Discussionmentioning
confidence: 60%
“…We previously observed that rats with unilateral ureter obstruction (UUO) induced-renal interstitial fibrosis (RIF) featured both ER stress ignition and Klotho loss, and Klotho replacement treatment repressed renal ER stress and improved their kidney function [20]. Furthermore, a recent study demonstrated that inhibition of ER stress rescued Klotho protein downregulation in mice with proteinuria CKD [21], suggesting a close link between ER stress and Klotho expression [22]. Persistent stress in CKD contributes to the continuous deposition of misfolded or unfolded proteins in the ER [23].…”
Section: Introductionmentioning
confidence: 99%